Dosificación de policloruro de aluminio en la sedimentación de lodo contaminado con hidrocarburos, en suelos de aguajal, del oleoducto Corrientes-Saramuro. Loreto, 2021 - Tello Sias, Danilo Joel (2024)
This research work was carried out in the environmental incident produced bya hydrocarbon spill, located at km 88+180 of the Corriente-Saramuro Pipeline of Lot 8, in the Loreto region, province of Loreto, district of Urarinas. The main objective was to determine the optimal dosage of Polyaluminum Chloride (PAC) in the sedimentation of sludge contaminated with hydrocarbons, the soil characteristic was taken into account, the experimental test method was the jug test. The statistical design was the DCR with thirty replications, the concentrations were 2.0 (t1), 2.5 (t2), 2.5 (t3) and 3.0 (T4), the experimental units were in disposable cups of 100 cc. The test statistic was Kruskal-Wallis, resulting in a significant difference for CAP concentrations in the sludge sedimentation in the sludge-water ratios (30:70 and 50:50) and sedimentation times (1.5 and 60 minutes). These results are referenced from the fact that the efficiency of the jar test is better the greater the sedimentation in the shorter time, thus, it is concluded that with a concentration of 2.0 cc of PAC for the suspension of sludge and water in proportions of 30:70 in a time of 1 minute the sedimentation is Furthermore, this jug test, its application in the treatment of soils in hydrocarbon-contaminated wetlands, could help minimize the environmental impact on ecosystems affected by oil spills, through environmental cleanup and remediation processes in the Peruvian Amazon.